All Conjugated Copolymer Excitonic Multiferroics. (22nd November 2012) - Lohrman, Jessica; Liu, Yueying; Duan, Shaofeng; Zhao, Xiaoyong; Wuttig, Manfred; Ren, Shenqiang
<x xml:space="preserve">Abstract</x> A substantial magnetoelectric coupling effect of an excitonic all‐conjugated block copolymer multiferroics consisting of electronically distinct polythiophene derivatives is reported. The observations open new avenues for the multifunctional all‐conjugated block copolymer synthesis and electric field tunable multiferroic devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>